Duodenal total and ionised calcium secretion in normal subjects, chronic alcoholics, and patients with various stages of chronic alcoholic pancreatitis. Issue 8 (August 1984) - Lohse, J; Pfeiffer, A
Abstract : Previous studies have shown increased secretion of total calcium in the duodenal juice of patients with chronic alcoholic pancreatitis compared with healthy subjects. In order to get more detailed information on calcium secretion and pancreatic stone formation in chronic alcoholic pancreatitis, ionised and total calcium concentrations were determined in the duodenal juice of normal subjects, chronic alcoholics, and patients with various stages of chronic alcoholic pancreatitis. Total calcium secretion was in agreement with previously published data. Chronic alcoholics presented a significant increase of ionised calcium. In the course of pancreatitis all calcium fractions increased progressively revealing highest concentrations in patients with severe exocrine insufficiency. In non-calcified and calcified pancreatitis all calcium fractions were identical. It is suggested that the increase of ionised calcium originates from serum ionised calcium passing by diffusion into the damaged pancreatic duct system.